1991
DOI: 10.1042/bj2730277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and control of degradation and resynthesis of adenylates in tumour cells

Abstract: A comparative study revealed that Ehrlich ascites carcinoma (EAC) cells use glutamine plus inosine for regeneration of adenylates via the purine nucleotide cycle, whereas AS 30D hepatoma cells use adenosine instead. This observation can be correlated with the very low production of aspartate from glutamine in hepatoma cells. Although glucose is an important energy fuel for EAC, it cannot maintain a high enough level of adenylates unless glutamine is also present. Kinetic analysis of hydrolysis of ATP and ADP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In particular, through aspartate, glutamine is essential for the synthesis of purine and pyrimidine bases as a carbon and nitrogen donor (22). This latter phenomenon seems to be important for the adaptation of tumors to transitions from the aerobic to the anaerobic state (23,24). Furthermore, it has been hypothesized that glutamine serves as an energy fuel through glutaminolysis (25), which seems to be a prerequisite for tumor cell growth (26).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, through aspartate, glutamine is essential for the synthesis of purine and pyrimidine bases as a carbon and nitrogen donor (22). This latter phenomenon seems to be important for the adaptation of tumors to transitions from the aerobic to the anaerobic state (23,24). Furthermore, it has been hypothesized that glutamine serves as an energy fuel through glutaminolysis (25), which seems to be a prerequisite for tumor cell growth (26).…”
Section: Discussionmentioning
confidence: 98%
“…Experiments with Ehrlich ascites carcinoma (EAC) cells supported this proposal [8]. Also, it was shown that the cells of AS 30D hepatoma do not use this pathway for the resynthesis of adenylates [9], and that they have a very low rate of synthesis of aspartate. This was the reason to undertake a detailed study of the pathways of glutamine oxidation, with the question why AS 30D hepatoma compared with EAC has much lower capability for synthesis of aspartate.…”
Section: Introductionmentioning
confidence: 95%
“…The high production of aspartate in EAC can be correlated with the regeneration of the pool of adenine nucleotides via the purine nucleotide cycle. Hepatoma cells do not use the same mechanism for resynthesis of AMP [9]. This suggests that in some tumour cell lines a high activity of the aspartate aminotransferase pathway might be important for resynthesis of adenylates and, therefore, for energy status of the cells.…”
Section: Consumption and Metabolism Of L-iu-'4clglutaminementioning
confidence: 99%